(untitled) (Bangladesh Journal of Pharmacology, 2022)
This study aims to examine the antianxiety and antidepressant effects of aqueous latex extract of Euphorbia resinifera in mice. Antianxiety and sedative effects were examined using the elevated plus maze test, open field test, and thiopental-induced sleeping time respectively. While the antidepressant effect was evaluated, using the forced swimming test. E. resinifera reduced the latency of sleeping and increased sleeping time significantly at 75 mg/kg. It reduced the immobility time and increased swimming significantly at all doses assessed (25, 50, and 75 mg/kg). Pretreatment with antagonists reversed these effects indicating the possible involvement of α2, 5HT2, D2, and GABAA receptors respectively. These findings confirm the traditional utilization of this plant as an antioxidant, anxiolytic, and antidepressant.